The Effect Of Sintering Temperature On The Hardness And Wear Tests Of Aluminum Matrix Composites Reinforced With Mwcnt Nanoparticles - setiawan, ferry; Wicaksono, Dhimas; Nur Hamzah, Muhammad (Universitas Muhammadiyah Ponorogo, 2025)
This study aims to investigate the effect of sintering temperature variations on the mechanical properties of Al-MWCNT composites produced by the powder metallurgy method. The matrix used was AA1100 aluminum with the addition of 1% nano Multi-Walled Carbon Nanotube (MWCNT). The mixture was compacted in a steel mold and sintered at temperatures of 450°C, 500°C, 550°C, and 600°C, and the results were compared with non-sintered specimens. The findings confirm that sintering at 500°C provides the most optimal results, as shown by a significant increase in hardness of 50.05 HV and improved wear resistance with a wear rate of only 0.4387 mm³/s, which is superior to the non-sintered specimens. EDS analysis revealed that this improvement is related to the lower oxygen content at 500°C, while SEM analysis showed tighter and more uniform particle bonding at this temperature. In contrast, sintering at temperatures above 500°C reduced material quality due to the formation of cracks and surface voids. These results clearly confirm that the increase in hardness and wear resistance of the material can only be achieved at the optimal sintering condition of 500°C.